Corrosion behavior of steel bar embedded in alkali-activated slag concrete subjected to carbonation and chloride attack (2012)
This paper presents an experimental study on the corrosion resistance of a steel bar embedded in an alkali-activated slag (AAS) concrete in which it was exposed to an accelerated carbonation test (3% CO2, 65% relative humidity (RH), and 25 ºC) and then tested under complete immersion in 3.5 wt. % NaCl solution. Ordinary Portland cement (OPC) was also tested for comparative purposes and was exposed to identical experimental conditions. The monitoring of open-circuit potential, the linear polarization resistance technique, and the electrochemical impedance spectroscopy (EIS), were used to evaluate the corrosion behavior of the steel bar. Corrosion resistance of carbonated AAS and OPC concretes was tested at different times. We carried out an exposure test of a solution containing Cl ions with all series for 0, 3, 6, 9, and 12 months. Electrochemical measurements show that AAS concrete presents depassivation of the steel embedded in concrete where it is exposed to accelerated carbonation; after this period of time, corrosion resistance decreased due to the presence of chlorides at the steel/AAS interface.